2017
DOI: 10.1016/j.neuroimage.2017.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Using multi-level Bayesian lesion-symptom mapping to probe the body-part-specificity of gesture imitation skills

Abstract: Past attempts to identify the neural substrates of hand and finger imitation skills in the left hemisphere of the brain have yielded inconsistent results. Here, we analyse those associations in a large sample of 257 left hemisphere stroke patients. By introducing novel Bayesian methods, we characterise lesion symptom associations at three levels: the voxel-level, the single-region level (using anatomically defined regions), and the region-pair level. The results are inconsistent across those three levels and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 50 publications
2
30
1
Order By: Relevance
“…Goldenberg & Karnath, 2006;Goldenberg & Randerath, 2015). However, some experimenters have failed to find a dissociation for brain regions related to defective hand and finger imitation (Achilles et al, 2017). It is also possible that the movement to attain the posture, rather than the final hand position alone, may be an important factor.…”
Section: Discussionmentioning
confidence: 99%
“…Goldenberg & Karnath, 2006;Goldenberg & Randerath, 2015). However, some experimenters have failed to find a dissociation for brain regions related to defective hand and finger imitation (Achilles et al, 2017). It is also possible that the movement to attain the posture, rather than the final hand position alone, may be an important factor.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the finger gestures require serial positioning of the digits with the hand position remaining consistent. Some have suggested that these tasks are strongly reliant on different areas of the brain (Goldenberg and Karnath 2006 ; Goldenberg and Randerath 2015 ; Goldenberg 2001 , 2009 ), whilst others propose a shared network (Achilles et al 2017 ). Our hand and finger gestures were not designed in keeping with these classical distinctions, and the focus on meaningless action in previous reports makes it hard for us to draw parallels with existing neuropsychological work (but see Achilles et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these retrospective analyses were approved by the institutional review board. Behavioural and lesion data of subsets of the current 293 patients were reported before in two other retrospective analyses comparing hand and finger imitation tests (n = 190, Achilles et al, 2017) and investigating the dissociation between MF and ML finger gesture imitation in LH and right hemisphere (RH) stroke at the behavioural level only (n = 132, Achilles et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…As described in Achilles et al (2017) all patients were assessed with the test of imitating finger gestures by Goldenberg (1996): the examiner sits opposite to the patient and demonstrates the ten finger gestures in a mirror-like fashion. The examiner uses the hand opposite to the patient's non-paretic ipsilesional hand, which the patient is supposed to use for the imitation.…”
Section: Methodsmentioning
confidence: 99%